Taking Stock of Descriptive-Interpretative Qualitative Psychotherapy Research: Issues and Observations from the Front Line. Counselling and Psychotherapy Research. - Timulak, Ladislav (My University, 2019)
The paper offers a perspective on some of the methodological issues present in current qualitative psychotherapy research (QPR). The authors are involved in this type of research (for 20 and 40 years, respectively) as researchers, as reviewers of papers submitted to journals publishing QPR, as well as past editors of such journals. The authors reflect at how the overall field of psychotherapy research has had an influence on how QPR is conducted. The authors further discuss a wide range of issues pertaining to QPR that often bring confusion in the community of psychotherapy researchers. These include: brand naming largely overlapping qualitative methods; epistemological confusion arising from the context and application of these methods; issues of data collection and the range of types of qualitative data; the confounding of investigative questions or aims with findings; the issue of interpretative frameworks in data analysis; strategies by which findings are generated; difficulties in assessing the representativeness of findings to the target sample; issues of generalisability of findings; and possibilities for developing cumulative knowledge across studies. The paper specifically focuses on those genres of qualitative research that have a descriptive–interpretative character, typically represented by brand‐name approaches such as empirical phenomenology, hermeneutics, interpretative phenomenological analysis, consensual qualitative research, grounded theory and thematic analysis, etc.
PUBLISHED
doi: 10.1002/capr.12197
Keywords: Qualitative psychotherapy research; Methodology; Research methods